Amino acid composition and nutritional value of seed proteins in sesame (Sesamum indicum L.) cultivars grown in Vietnam - Huyen, T. T. T.; Mui, N. V.; Bang, C. P. (International Journal of Agricultural Technology, 2016)
Seeds of six sesame cultivars collected from different provinces of Vietnam were used for the research. The sesame seeds were selected, dehydrated, ground and stored at 4oC for analyses. The samples were hydrolyzed. The analysis of total amino acid contents and amino acid composition were carried out with precolumn derivatization technique (in HP - Amino Quant Series II, Hewlett Packard) using ortho-phthadialdehyd (OPA) for primary amino acids and 9-fluorenyl methyl chloroformat (FMOC) for secondary amino acids. The results shown that the total seed amino acid contents of the six cultivars ranged from 17.25 to 21.98%. Among six cultivars, the highest total amino acid contents was were observed in seed of two cultivars, V5 (21.98%) and V14 (21.60%). The seeds of V8 cultivar contained the smallest total amino acid contents (17.25%). All essential amino acids were found in the seeds of six examined sesame cultivars. The contents of these amino acids in seed proteins were approximate or higher in compared to FAO standard protein. The seed proteins of these six sesame cultivars had good nutritional values based on the high content of essential amino acids, lysine and leucine especially.